Making a Housing Market in Paris - BLACKMAR, ELIZABETH (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
Alexia Yates’ Selling Paris renders in satisfying empirical detail the agents and institutions, especially the joint-stock sociétés anonymes, that in the last third of the nineteenth century fashioned the Parisian housing market on a new scale, from financing and land acquisition to the management of apartment buildings as investment properties. In its penetrating and exemplary analysis, Selling Paris is destined to anchor new comparisons of the impact of different legal regimes, institutions of finance and real estate enterprise, and balances of public and private power on housing markets and built environments in other cities and nations. By showing how Parisian developers themselves framed a narrative of urban housing as “merchandise” in order to legitimate their financial speculations, Yates also offers her readers critical distance on that paradigm and its associated tendency to treat the social politics as expressions of consumer rights.